A Framework for Climate Change Risk Management Practice and Performance of Financial Institutions in Saudi Arabia - Sarabdeen, Masahina (Universitas Syiah Kuala, 2022)
Objective Increasing intensity and severity of extreme weather events are threatening economic resilience and longer-term prosperity. Therefore, a framework for effective climate change risk management is required to manage the climatic challenges and preserve the long-term presence of financial institutions. The purpose of this paper is to design a conceptual framework for determining the level of climate change risk management (CCRM) practice, and understanding of CCRM. It also aims to identify CCRM valuation and analysis, and CCRM monitoring and regulating in financial institutions, particularly in Saudi Arabias finance organizations. It further aims to investigate the relationship between CCRM practice and financial performance.Design/methodology The paper reviews and synthesises the relevant literature on climate change risks and management, and financial institutions. A conceptual framework for managing climate change risks is then developed and proposed in the paper.Results Using this conceptual paper as a starting point for empirical research, we will examine CCRM practices among financial institutions. It is hoped to fill a knowledge and method gap.Research limitations/implications The knowledge obtained from this study hopes to support the supervision of CCRM among the financial institutions and internal control system to meet the requirements of The Intergovernmental Panel on Climate Change to manage climate change risk in Saudi Arabia.Novelty/originality In this study, the originality lies in the fact that previous studies have only examined financial practices among financial institutions. Studies on climate change risk management practice have not yet been carried out.